2020
DOI: 10.1093/cid/ciaa801
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for RecurrentStaphylococcus aureusBacteremia

Abstract: Background To understand the clinical, bacterial, and host characteristics associated with recurrent Staphylococcus aureus bacteremia (R-SAB), patients with R-SAB were compared to contemporaneous patients with a single episode of SAB (S-SAB). Methods All SAB isolates underwent spa genotyping. All isolates from R-SAB patients underwent pulsed-field gel electrophoresis (PFGE). PFGE-indistinguishable pairs from 40 patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Population-based studies conducted in many jurisdictions globally have identified Staphylococcus aureus as the second most common cause of bloodstream infection (BSI) occurring with an annual incidence of approximately 30-40 per 100,000 population and an associated case-fatality rate of 20% (El Atrouni et al, 2009;Huggan et al, 2010;Lam et al, 2019;Laupland et al, 2013;Laupland et al, 2008;Opintan and Newman, 2017). Due in part to a propensity for complications related to metastatic foci, anti-microbial resistance, and risk for relapse, S. aureus BSI is associated with high morbidity and mortality (Choi et al, 2020). To reduce this burden, guidelines and algorithms that involve use of echocardiography, repeat blood cultures, and detailed clinical decision-making including antimicrobial source and route and duration of administration have been developed (Chong et al, 2013;Holland et al, 2018;Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Population-based studies conducted in many jurisdictions globally have identified Staphylococcus aureus as the second most common cause of bloodstream infection (BSI) occurring with an annual incidence of approximately 30-40 per 100,000 population and an associated case-fatality rate of 20% (El Atrouni et al, 2009;Huggan et al, 2010;Lam et al, 2019;Laupland et al, 2013;Laupland et al, 2008;Opintan and Newman, 2017). Due in part to a propensity for complications related to metastatic foci, anti-microbial resistance, and risk for relapse, S. aureus BSI is associated with high morbidity and mortality (Choi et al, 2020). To reduce this burden, guidelines and algorithms that involve use of echocardiography, repeat blood cultures, and detailed clinical decision-making including antimicrobial source and route and duration of administration have been developed (Chong et al, 2013;Holland et al, 2018;Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no studies that directly compare the performance of WGS to that of ERIC-PCR, so the quantitative difference in resolution between these two methods is unknown. A study of recurrent Staphylococcus aureus bacteremia showed that the amount of SNP variation by WGS is consistent with the PFGE, and authors concluded that no novel insights were provided by WGS in the study ( 26 ). Although the result may not be applicable to our study because of the difference in the species of bacteria studied, as for repeated bacteremia in a single patient, the result of WGS may be consistent with that of PCR-based typing techniques, which has lower discrimination power compared to WGS.…”
Section: Discussionmentioning
confidence: 99%
“…A prompt and accurate identification of the causative pathogens of a bacterial infection is essential for providing patients with adequate treatments to reduce mortality and to prevent antibiotic resistance (1)(2)(3)(4). Bacterial infections caused by the human pathogenic bacteria Staphylococcus aureus and Streptococcus pneumoniae remain highly prevalent (5)(6)(7)(8). Despite the development and availability of antibiotics, mortality remains high, reaching 20 % for S. aureus associated endocarditis and more than one million deaths of children below 5 years of age by S. pneumoniae (5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infections caused by the human pathogenic bacteria Staphylococcus aureus and Streptococcus pneumoniae remain highly prevalent (5)(6)(7)(8). Despite the development and availability of antibiotics, mortality remains high, reaching 20 % for S. aureus associated endocarditis and more than one million deaths of children below 5 years of age by S. pneumoniae (5,7).…”
Section: Introductionmentioning
confidence: 99%